Systems of equations of Kolmogorov type - Malyts’ka, H. P. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We consider one class of degenerate parabolic systems of equations of the type of diffusion equation with Kolmogorov inertia. For systems whose coefficients may depend only on the time variable, we construct a fundamental matrix of solutions of the Cauchy problem and obtain estimates for this matrix and all its derivatives.